Local peer effects and corporate investment - Yangming Bao; Martin Goetz (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
We examine how a firms' investment behavior affects the investment of a neighboring firm. Economic theory yields ambiguous predictions regarding the direction of firm peer effects and consistent with earlier work, we find that firms display similar investment behavior within an area using OLS analysis. Exploiting time-variation in the rise of U.S. states' corporate income taxes and utilizing heterogeneity in firms' exposure to increases in corporate income tax rates, we identify the causal impact of local firms' investments. Using this as an instrumental variable in a 2SLS estimation, we find that an increases in local firms' investment reduces the investment of a local peer firm. This effect is more pronounced if local competition among firms is stronger and supports theories that firm investments are strategic substitutes due to competition.
urn:nbn:de:hebis:30:3-472046
Keywords: G31; G38; 330; Investments; Peer Effects; Agglomeration; Corporate Income Tax